Masks of the lyrical subject in nicaraguan poetry (1979-1986) - Zosa-Cano, Alexander (2025)
Poetry is the vehicle where a range of individual emotions and frustrations are transmitted from the individual to the collective field. This poetry is in any space and circumstance, and has served to organize memories and ultimately the reconstruction of memory. This article aims to analyze these manifestations: the evasion of the collective memory referent and the appropriation of national identity as masks of the lyrical subject in Nicaraguan political poetry. A sample of poetic texts published by four writers was used: Octavio Robleto, Edwing Castro Rodriguez, Amed Campos and Guillermo Rothschuh Tablada between 1979 and 1986. From the sample of the texts, the behavior of the writers in the aforementioned directions will be evidenced, and how in other cases the representation of the evasion of the referent that serves as a mask to connect with the readers is conjugated. In addition, it is evident through this poetic sample has the psychological intent to hide the referent (mask of the lyrical subject). Testimonial poetry appropriated the cultural elements to evidence the marked difference that exists between the working class and the bourgeoisie, and thus be able to connect with the readers.